Biological effects of basic fibroblast growth factor (bFGF) and osteogenic protein-1 (OP-1/BMP-7) on bone marrow cells and development of cell-hybrid artificial bone - Higashinakagawa, M (Kōkūbyō Gakkai Zasshi, 1999)
In this study, the effects of bFGF and OP-1 on rat bone marrow cells and bone formation by the cultured bone marrow cells in porous hydroxyapatite (HA) in subcutaneous sites of syngeneic rats were investigated. The effects of bFGF and OP-1 on the proliferation and the differentiation of rat bone marrow cells were investigated by means of measurement of [3H] thymidine incorporation into DNA, ALP activity and bone nodule formation. This in vitro study showed that both bFGF and OP-1 increased [3H] thymidine incorporation, especially bFGF which stimulated it 3.5-fold at a dose of 30ng/ml. OP-1 stimulated ALP activity and bone nodule formation, whereas bFGF suppressed them. These data suggested that bFGF stimulates proliferation of rat bone marrow cells and OP-1 accelerates their differentiation. These growth factors were used to fabricate cell hybrid artificial bone, which consisted of the bone marrow cells. The ectopic bone formation was induced by the bone marrow cells cultured in HA, regardless of the treatment of these growth factors. However, the histological analysis revealed that the treatment with bFGF and/or OP-1 increased the area of new bone formation and accelerated the maturation of bone compared with the controls. The results suggested that the bone marrow cells cultured in HA three-dimensionally could be used clinically as a biomaterial. Furthermore, the use of bFGF and OP-1 to produce this cell-hybrid artificial bone increases its bone forming activity.